Penerapan Bahasa Inggris Terintegrasi Dengan Pembelajaran Di TPQ Al-Mataab Desa Tembokrejo – Muncar – Banyuwangi - Roudlotun Nurul Laili; Muhammad Nashir (Bahasa Indonesia, 2018)
As one of world languages, English is broadly used in many aspects such as science, business, technology, and education. Thus English is highly necessary to be introduced as soon as possible to the students in order to compete in the globalization era. The purpose of this community service activity is to integrate the English material in the curriculum of TPQ (Al-Qur’an Learning Center), so the students can know earlier about English as a global language. This activity was conducted at TPQ Al-Mataab - Tembokrejo – Muncar – Banyuwangi in which the classes were divided into two, they are class A (students aged 7-10) and class B (students aged 11-14). The methods used were drilling, flashcard, and songs in training and giving Basic English materials to the students. Some steps in performing this activity were preparation, conducting pre test to find out the initial of students’ English ability, training and teaching, and giving post test to know the progress of the activity. The mean score result of class A showed the enhancement from 43.89 in pre test to 62.41 in post test. While in class B the pre test result was 61.4 and in post test increase into 71.6. It indicated that students are eager and excited in learning English and it is feasible and potential to be integrated in TPQ curriculum.